2006
DOI: 10.1007/s11883-006-0036-6
|View full text |Cite
|
Sign up to set email alerts
|

Statins and the primary prevention of cardiovascular events

Abstract: Cardiovascular disease remains the leading cause of death in both men and women in the United States. Treating elevated low-density lipoprotein (LDL) cholesterol has been shown to be very effective in reducing the rate of coronary heart disease (CHD) in primary prevention trials; however, the data are not as robust for treating individuals categorized at either lower risk for CHD or with below-average LDL cholesterol levels. The next frontier for investigation will include strategies to determine who in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 40 publications
0
10
0
2
Order By: Relevance
“…Control of cholesterol levels through therapeutic drugs have significantly reduced the risk of developing atherosclerosis and associated cardiovascular diseases [7,8,9,10]. Notably, statins, a class of cholesterol-lowering drugs inhibiting cholesterol synthesis, have been most widely prescribed for treating hypercholesterolemia and reducing cardiovascular diseases [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Control of cholesterol levels through therapeutic drugs have significantly reduced the risk of developing atherosclerosis and associated cardiovascular diseases [7,8,9,10]. Notably, statins, a class of cholesterol-lowering drugs inhibiting cholesterol synthesis, have been most widely prescribed for treating hypercholesterolemia and reducing cardiovascular diseases [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, statins, a class of cholesterol-lowering drugs inhibiting cholesterol synthesis, have been most widely prescribed for treating hypercholesterolemia and reducing cardiovascular diseases [8,9,10]. However, adverse effects associated with therapeutic drugs, such as myopathy, liver damages and potential drug-drug interaction, have been reported [11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the low absolute event rates in those with both low LDL-C and CRP in AFCAPS/TexCAPS, the JUPITER investigators concluded that overall this group would not benefit from statin therapy, and thus excluded them from the study cohort. However, a post hoc analysis of AFCAPS/ TexCAPS suggested the hypothesis that primary prevention patients at LDL-C goal (ie, <130 mg/dL) but with metabolic syndrome and a CRP geater than 1 mg/L may also benefit from lovastatin therapy (RR 0.62; P=0.315) [14]. Because the number of individuals in this subgroup was small, the statistical benefit was not confirmed but trended toward benefit, thus generating the hypothesis that this may be a subgroup who might benefit from statin therapy.…”
Section: Commentsmentioning
confidence: 99%
“…Varios ensayos aleatorizados de prevención secundaria y primaria han permitido analizar el efecto de las intervenciones hipolipemiantes con estatinas [752][753][754] . Aunque los datos epidemiológicos indican que la concentración sérica de colesterol presenta una estrecha asociación con los episodios coronarios pero no con el ictus 755 , las estatinas han resultado eficaces para prevenir tanto los episodios coronarios como los cerebrovasculares, y la prevención de ambos trastornos es similar en pacientes hipertensos y normotensos [752][753][754] .…”
Section: Fármacos Hipolipemiantesunclassified
“…Aunque los datos epidemiológicos indican que la concentración sérica de colesterol presenta una estrecha asociación con los episodios coronarios pero no con el ictus 755 , las estatinas han resultado eficaces para prevenir tanto los episodios coronarios como los cerebrovasculares, y la prevención de ambos trastornos es similar en pacientes hipertensos y normotensos [752][753][754] . En el ensayo aleatorizado más amplio realizado hasta el momento con una estatina, el Heart Protection Study 756 , la administración de simvastatina a pacientes con una enfermedad cardiovascular establecida redujo 62e Rev Esp Cardiol.…”
Section: Fármacos Hipolipemiantesunclassified